THE EFFECT OF INTERNAL AUDIT, ANTI-FRAUD STRATEGY, AND DISCLOSURE OF RISK MANAGEMENT IN THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN ISLAMIC BANKING - Nasution, Muhammad Syafril (2021)
The purpose of this study was to determine the effect of internal audit, anti-fraud strategy, and risk management disclosure in the implementation of good corporate governance in Islamic banking. This study uses a quantitative method. The population in this study were all Islamic banking units (Islamic Commercial Banks) in Indonesia which were selected using the purposive sampling method. The data sources in this study are secondary data, financial statements, and Islamic bank CGC reports. Analysis of research data using F test, Coefficient of Determination test (R2), and t-test. Based on the results of research and data processing, it can be concluded that: 1) Internal Audit has no positive and significant effect on the implementation of Good Corporate Governance in Islamic Banking with a tcount of -1.794 (> ttable) with a significance value of 0.078 (sig > 0.05); 2) Anti-Fraud Strategy has a positive and significant impact on the implementation of Good Corporate Governance in Islamic Banking with a tcount of 2.173 (> ttable) with a significance value of 0.034 (sig < 0.05); and 3) Risk Management Disclosure has a positive and significant effect on the implementation of Good Corporate Governance in Islamic Banking by obtaining a t count of 2.173 (> t table) with a significance value of 0.034 (sig < 0.05).